2022
DOI: 10.1002/ima.22703
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning‐based automated mitosis detection in histopathology images for breast cancer grading

Abstract: Cancer grade is an indicator of the aggressiveness of cancer. It is used for prognosis and treatment decisions. Conventionally cancer grading is performed manually by experienced pathologists via microscopic examination of pathology slides. Among the three factors involved in breast cancer grading (mitosis count, nuclear atypia, and tubule formation), mitotic cell counting is the most challenging task for pathologists. It is possible to automate this task by applying computational algorithms on pathology slide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Khan et al [12] introduced the SMDetector, a DL technique in which the dilated layers aim to reduce the size gap between the images and objects. Mathew et al [13] suggested a novel method based on a class imbalance phenomenon which is understood by the growth of mitotic cells in a context-preserving way. Eventually, the adapted CNN algorithm was employed for the classification of the candidate cells into target class labels.…”
Section: Related Workmentioning
confidence: 99%
“…Khan et al [12] introduced the SMDetector, a DL technique in which the dilated layers aim to reduce the size gap between the images and objects. Mathew et al [13] suggested a novel method based on a class imbalance phenomenon which is understood by the growth of mitotic cells in a context-preserving way. Eventually, the adapted CNN algorithm was employed for the classification of the candidate cells into target class labels.…”
Section: Related Workmentioning
confidence: 99%
“…Binary Acc = 99% Avg. Multiclass Acc = 95% Mathew et al [ 289 ] 2022 Breast Cancer Cell Detection/Classification CNN ATYPIA MITOS F1 score = 61.91% Singh and Kumar [ 290 ] 2022 Classification Inception ResNet BHI BreakHis BHI: Acc = 85.21% BreakHis: Avg. Acc = 84% Mejbri et al [ 291 ] 2019 Tissue-level Segmentation DNNs Private U-Net: Dice = 86%, SegNet: Dice = 87%, FCN: Dice = 86%, DeepLab: Dice = 86% Guo et al [ 292 ] 2019 Cancer Regions Segmentation Transfer learning based on Inception-V3 and ResNet-101 Camelyon16 IOU = 80.4% AUC = 96.2% Priego-Torres et al [ 271 ] 2020 Tumor Segmentation CNN Private Acc = 95.62% IOU = 92.52% Budginaitė et al [ 293 ] 2021 Cell Nuclei Segmentation Micro-Net Pri...…”
Section: Artificial Intelligence In Medical Image Analysismentioning
confidence: 99%